A homozygous variant in CHMP3 is associated with complex hereditary spastic paraplegia. Issue 3 (16th June 2022) - Cohen-Barak, Eran; Danial-Farran, Nada; Chervinsky, Elana; Alimi-Kasem, Ola; Zagairy, Fadia; Livneh, Ido; Mawassi, Bannan; Hreish, Maysa; Khayat, Morad; Lossos, Alexander; Meiner, Vardiella; Ehilevitch, Nina; et al.
Abstract : Background: Monogenic neurodegenerative diseases represent a heterogeneous group of disorders caused by mutations in genes involved in various cellular functions including autophagy, which mediates degradation of cytoplasmic contents by their transport into lysosomes. Abnormal autophagy is associated with hereditary ataxia and spastic paraplegia, amyotrophic lateral sclerosis and frontal dementia, characterised by intracellular accumulation of non-degraded proteins. We investigated the genetic basis of complex HSP in a consanguineous family of Arab-Muslim origin, consistent with autosomal recessive inheritance. Methods: Exome sequencing was followed by variant filtering and Sanger sequencing for validation and familial segregation. Studies for mRNA and protein expression used real-time PCR and immunoblots. Patients' primary fibroblasts were analysed using electron microscopy, immunofluorescence, western blot analysis and ectopic plasmid expression for its impact on autophagy. Results: We identified a homozygous missense variant in CHMP3 (Chr2:86507484 GRCh38 (NM_016079.4): c.518C>T, p.Thr173Ile), which encodes CHMP3 protein. Segregation analysis validated the presence of the homozygous variant in five affected individuals, while healthy family members were found either heterozygous or wild type for this variant. Primary patient's fibroblasts showed significantly reduced levels of CHMP3. Electron microscopy disclosed accumulation of endosomes, autophagosomes and autolysosomes in patient's fibroblasts, which correlated with higher levels of autophagy markers, p62 and LC3-II. Ectopic expression of wild-type CHMP3 in primary patient fibroblasts led to reduction of the p62 particles accumulation and number of endosomes and autophagosomes compared with control. Conclusions: Reduced level of CHMP3 is associated with complex spastic paraplegia phenotype, through aberrant autophagy mechanisms.